Pengaruh Brand Image, Online Consumer Review, dan Harga Terhadap Keputusan Pembelian Smartphone Oppo Pada Mahasiswa FEB Universitas Trunojoyo Madura - Saputri, Septia Dea; Purnomo, Hadi (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
This study is driven by the decline in Oppo smartphone purchases. The aim of this research was to analyze the impact of brand image, online consumer reviews, and price on the purchasing decisions of Oppo smartphones. The participants in this study were FEB students from Trunojoyo Madura University who use Oppo smartphones. This research employs quantitative methods using both primary and secondary data. The sampling method applied was purposive sampling with a total of 96 respondents. Data collection was conducted using a questionnaire that had been validated and tested for reliability. The study utilized multiple linear regression analysis with the assistance of the SPSS 24 program. The partial test results indicated that the brand image variable influenced purchasing decisions, the online consumer review variable did not affect purchasing decisions, and the price variable had an impact on purchasing decisions. The simultaneous test results showed that brand image, online consumer reviews, and price significantly influenced purchasing decisions.